Accuracy of the International Academy of Cytology Yokohama system of breast cytology reporting for fine needle aspiration biopsy of the breast in a dedicated breast care setting. Issue 2 (5th October 2020) - Agarwal, Akansha; Singh, Divya; Mehan, Anoushika; Paul, Pranoy; Puri, Neeti; Gupta, Priyanka; Syed, Anjum; Rao, Shalinee; Chowdhury, Nilotpal; Ravi, Bina
Abstract: Background: The International Academy of Cytology (IAC) Yokohama system is a recently proposed system for reporting breast cytology by fine needle aspiration biopsies (FNAB). Multiple studies are needed to confirm the risk of malignancy (ROM) of the various reporting categories of this system. The present article studies the accuracy of the IAC Yokohama system in our center. Methods: Over a period of 1 year (September 2018‐August 2019), all cases of breast masses assessed by FNAB and histological correlation were studied retrospectively. Sensitivity, specificity, negative predictive value (NPV) and positive predictive value (PPV) and overall accuracy of the IAC Yokohama system for diagnosing malignancy were assessed. The rates of malignancy (ROM) of each diagnostic category were also estimated. Results: Three hundred and twenty‐one FNABs had cyto‐histological correlation. The percent sensitivity (with 95% Confidence Intervals) when the atypical, suspicious of malignancy and the malignant categories were regarded as positive for malignancy were 98.2% [95.5%, 99.5%], 96.0% [92.5%, 98.2%], and 86.7% [81.5%, 90.8%] respectively. The percent specificity (with 95% Confidence intervals) for the same categories in the same order were 59.5% [47.4%, 70.7%], 91.9% [83.2%, 97.0%], and 100% [95.1%, 100%] respectively. The area under curve (AUC) for diagnosing malignancy was 0.981[0.963, 0.993]. The ROM for the benign, atypical, suspicious of malignancy and malignant category were 8.3% [2.3%, 20.0%], 17.2% [5.8%, 35.8%], 77.8% [57.7%, 91.4%], and 100% [98.1%, 100%] respectively. Conclusion: The IAC Yokohama system is suitable for accurately reporting breast lesions on FNAB.